Determinants of stunting in school-aged children of Tehran, Iran - Fatemeh Esfarjani; Roshanak Roustaee; Fatemeh Mohammadi; Ahmad Esmaillzadeh (International Journal of Preventive Medicine, 2013)
Background: Limited data are available indicating associates of stunting among Iranian children. This study was conducted to investigate determinants of stunting in first grade primary school children of Tehran in 2007. Method: In this case-control study, 3147 school children were selected by multistage cluster random sampling method from 5 districts of Tehran. Anthropometric measurements were done and stunting was defined as height for age less than the 5 th percentile of CDC2000 cut-off points. Eighty six stunted children were identified and considered as case group. After matching for age, sex and residence area, 308 non-stunted children were randomly selected as control group. Required data were collected by trained nutritionists using questionnaires. Results: Stunting was prevalent among 3.7% of the study population (girls 4.4% vs. boys 2.8%, P < 0.05). Mean age of the studied children was 82.3 month. Children with a birth weight of >3000 g were less likely to be stunted (OR: 0.25: 95% CI: 0.11-0.54) compared with those with a birth weight of <3000 g. Being born to older mothers (>35 years) was associated with greater odds of being stunted (3.01; 1.19-7.60) compared with being born to younger mothers (<35 years). Those with fathers′ height of >160 cm were less likely to be stunted (0.04; 0.005-0.37) than those whose fathers′ height was less than 160 cm. Conclusions: We found that birth weight, maternal age and fathers′ height are the major contributing factors to stunting in this group of Iranian children. Taking into account the determinants of stunting might help policy makers designing appropriate interventions.